2023
DOI: 10.3390/antiox13010057
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Functions of High-Density Lipoprotein in Type 1 and Type 2 Diabetes

Damien Denimal

Abstract: (1) Background: high-density lipoproteins (HDLs) exhibit antioxidant and anti-inflammatory properties that play an important role in preventing the development of atherosclerotic lesions and possibly also diabetes. In turn, both type 1 diabetes (T1D) and type 2 diabetes (T2D) are susceptible to having deleterious effects on these HDL functions. The objectives of the present review are to expound upon the antioxidant and anti-inflammatory functions of HDLs in both diabetes in the setting of atherosclerotic card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 199 publications
0
5
0
Order By: Relevance
“…HDL has a pleiotropic function [47,48], including antioxidant [49] and antiinflammatory [50] properties, and is well associated with cardiovascular health [51]; though, HDL involvement in various healthy and pathological conditions is also well described [52,53]. The present study outcome revealed a substantial effect of OSO consumption on enhancement of blood antioxidant ability and HDL functionality.…”
Section: Discussionmentioning
confidence: 54%
“…HDL has a pleiotropic function [47,48], including antioxidant [49] and antiinflammatory [50] properties, and is well associated with cardiovascular health [51]; though, HDL involvement in various healthy and pathological conditions is also well described [52,53]. The present study outcome revealed a substantial effect of OSO consumption on enhancement of blood antioxidant ability and HDL functionality.…”
Section: Discussionmentioning
confidence: 54%
“… 15 , 18 , 32 On the other hand, HDL-C serves a crucial anti-inflammatory role. 52 A decline in HDL-C concentrations heightens the inflammatory status within the body. In essence, the association between prediabetes and MHR likely stems from inflammation, which reinforces the potential value of MHR in prediabetes, particularly in assessing the risks associated with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings prompt further exploration into the potential mechanisms underlying the association between low HDL levels and heightened inflammation. HDL is known for its antiinflammatory and antioxidant properties and its role in cholesterol efflux, which is the process of removing excess cholesterol from cells, including immune cells [19,20]. In the context of long COVID persistent low HDL levels may lead to a dysregulated immune response, resulting in an amplified and prolonged inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…This is because HDL modulates the function of immune cells and inhibits the production of pro-inflammatory cytokines [17,20]. When HDL levels are low, cholesterol can build up within immune cells, potentially triggering inflammatory pathways and contributing to an exaggerated inflammatory response [19]. This dysregulation may be particularly pronounced in long COVID, where the immune system is dealing with persistent viral effects.…”
Section: Discussionmentioning
confidence: 99%